PEMANFATAAN DATA EQUATORIAL ATMOSPHERE RADAR (EAR) DALAM MENGKAJI TERJADINYA MONSUN DI KAWASAN BARAT INDONESIA(THE VALUABLE OF EQUATORIAL ATMOSPHERE RADAR (EAR) DATA TO STUDY MONSOON IN THE WEST AREA INDONESIA) - Veza Azteria; Sobri Effendy; Eddy Hermawan (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2008)
Kototabang, Padang Panjang and Sicincin city are area in the West part of Indonesia and they are relative in the equator line. Otherwise, three of these cities have difference of behaviors of rainfall for Monsoon. In this study, we were used EAR Data, which were including the rainfall Kototabang, Padangpanjang, and Sicincin. Base on this data (i.e EAR data) in Kototabang, there is monsoon in 8-18 km layer and the higher monsoon is in 14 km layer during the April 2002-April 2006 period. Analisis Power Spectral Density (PSD) and Transformasi wavelet were shown that Monsoon oscillation around 12 months. While vertical profile was presented that the stronger monsoon will be in the wet weather on January. The domination of wind in Kototabang city is South Wind, it is because the wind took water vapor mass from South to North. According to analysis of rainfall in Kototabang, Padangpanjang and Sicincin City, meridional wind in the the Sicincin has rainfall pattern the same as with monsoon. Its was indicated that there were local indicator which can cause the monsoon. From the cross correlation between meridionial wind speed with rainfall in Kototabang, Pontianak and Sicincin, they were shown that three of these cities have significant correlation.